Bottom-Up Cross-border planning - Medeiros, E. (CESCI 10y Anniversary Conference, 2019)
Cross-Border Planning can be generically understood as ‘systematic preparation and implementation of a spatial-oriented policy or plan, in a border region, with a view to anticipating spatial changes, and in order to have direct or indirect positive effects on spatial activities, with the ultimate goal of reducing the barrier effect and enhancing territorial capital’. To be implemented in a more effective way, however’ it should take into account the concerns and experiences from cross-border dwellers and commuters, via a collection of individual questionaries’ on issues related with their daily lives. In this presentation will debate how this bottom-up cross-border planning process could be further developed for improving the quality of life in cross-border areas.